Risk and environmental allocation - Horst Siebert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1987)
Uncertainty is an important aspect of the environmental issue quite a few of the basic functions describing the role of the environment for the economic system are not well known "ex ante". Emissions interact through rather complex and intricate systems and pollutants such as DDT accumulate through natural chains in a way that often is only discovered "ex post" with some delay. Variables Strategie for the analysis of environmental allocation can therefore be considered as random variables. Pollutants as a by-product of our economic activities include the risk of potentially generating negative environmental impacts in the future. Risk of environmental effects may relate to small scale issues such as the eutrophication of a pond or to global problems as the heavily debated greenhouse effect from an increase in carbon dioxide or the destruetion of the ozone layer. The problem arises what types of risk exist in using the environment, how these risks will influence environmental use if some optimal environmental quality is strived for, what implications will follow for environmental policy instruients and how the costs of risk reduetion should be allocated to the decentral subsystems of a society.
Keywords: 330; Risiko; Umweltökonomik